Study of a Thermoelectric Air Duct System Assisted by Photovoltaic Wall for Space Cooling In Tropical Climate - Kashif, Irshad; Khairul, Habib; F., Basrawi; Saha, Bidyut Baran (Elsevier Ltd, 2017)
The integration of building structure with renewable components such as photovoltaic (PV) panel and thermoelectric modules (TEMs), provides new opportunities for exploiting natural energy and minimizing impact on the environment. This paper presents experimental and simulation investigation of a novel thermoelectric air duct system (TE-AD) assisted with photovoltaic (PV) system for space cooling in Malaysian weather condition. The north facing TE-AD system consist of fifteen TEMs assisted by 300 Wp south wall facing PV system for cooling of test room whose volume is 9.45 m3. Both simulation and experimental results were in good agreement and showed that PV assisted TE - AD system when operated at 6 A gives the optimum temperature difference of 6.8 °C with cooling capacity of 517.24 W and COP of 1.15. Combination of the TE-AD and PV system saves 1806.75 kWh/year with an additional benefit of Freon free, highly reliable and less fossil fuel consuming system.